An RBC model with Epstein-Zin (non-expected-utility) recursive preferences: lessons from Bulgaria (1999-2016) - Aleksandar Vasilev (ZBW – Leibniz Information Centre for Economics, 2018)
We introduce Epstein-Zin (1989, 1991) preferences into a real-business-cycle setup augmented with a detailed government sector. We calibrate the model to Bulgarian data for the period following the introduction of the currency board arrangement (1999-2016). We investigate the quantitative importance of the presence of "early resolution of uncertainty" motive for the propagation of cyclical fluctuations in Bulgaria. Allowing for Epstein-Zin preferences improves the model performance against data, and in addition this extended setup dominates the standard RBC model framework, e.g., Vasilev (2009).
Keywords: E32; E22; E37; 330; business cycle fluctuations; Epstein-Zin preferences; Bulgaria